Indigenous perspectives on integrating learning technologies in a tertiary enabling program - Matthews, Aaron; Aggarwal, Rachna; Flintoff, Kim; Turnbull, Mattie (2015)
The Centre for Aboriginal Studies at Curtin University offers an Indigenous Tertiary Enabling Course designed to equip Indigenous students for entry into mainstream university degree programs. While the program is highly regarded, it is argued that opportunities offered by incorporating contemporary learning technologies to allow more effective student engagement can deliver more successful outcomes. With this in mind the Centre has undertaken to introduce the use of tablet devices (iPad) and notebook computers (MacBook Air), which will enable a strategic shift towards a more student-centred, technology, integrated model of student engagement with anticipated enhanced outcomes. The Centre has undertaken to trial the use of online teaching and learning strategies in semester 1, 2014. At this pre-tertiary level, it is anticipated the advantages of a student-centred experience will become evident as the trial moves through the year. This paper describes the current conditions and staff perceptions after the first year of implementation as well as comparing outcomes from the most recent ITEC cohort.